Strategi Penanggulangan Bullying di Lingkungan Sekolah Dasar: Tinjauan Kasus dari Perspektif Siswa dan Guru di UPT SDN 060839 Medan - Tambunan, Mona Yuniar; Sihombing, Natasya; Sitanggang, Nanda Septanya; Sitanggang, Yohana Gabriella (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Bullying in the elementary school environment has become a serious issue that affects students' well-being and the overall atmosphere at the school. At UPT SDN 060839 Medan, the challenge of bullying is also a major concern for the school community, due to its detrimental impact on academic achievement, mental well-being, and the quality of the learning experience student. This research aims to present an in-depth case review of bullying prevention strategies in the UPT SDN 060839 Medan Elementary School environment, with a focus on the views and direct experiences of students and teachers. This study uses a qualitative method. Data collection techniques use observation and interviews. Teachers' perception of bullying is a serious problem, teachers express their seriousness in responding to bullying behavior which is predicted by the seriousness they feel, such as empathy for their students to overcome it, where teachers support the implementation of awareness and education regarding bullying. Students' feelings after bullying are pity, regret, pity and also unnatural. The forms of bullying in elementary schools are as follows: (1) Physical bullying (2) Verbal bullying (3) Mental bullying. It was concluded that bullying is a serious problem in elementary schools that can have a negative impact on victims, perpetrators and witnesses. Bullying is an act of crime and bad behavior that torments other people, is an act of violence, abuse and unpleasant actions.